The Contribution of Internet Utilization towards the Student Learning Outcomes - Efendi, Sapran; Yusuf, A. Muri; Solfema, Solfema (Jurnal Aplikasi IPTEK Indonesia, 2021)
The emergence of the internet has a major effect on human life, including in education. The internet contributes to academics so that it has a very important role for student learning success. This research aims to describe the contribution of internet utilization as a learning resource towards the student learning outcomes at SMA Negeri 2 Padang. This study used a descriptive quantitative research method, and the data were analyzed by using the simple linear regression. The population of this research was 920 students of SMA Negeri 2 Padang, and the sample chosen was 279 students selected by using the proportional random sampling technique. The research instrument used was a scale of internet utilization with a Likert model. The findings of this research showed that the use of the internet as a learning resource contributes towards the student learning outcomes at SMA Negeri 2 Padang with an effective contribution 40.4%.